Diagnostic study of selected types of cardiac arrhythmias of dogs - Mohamed Elsaid Abdelrahman Ali; Adel Abdelbaset M. Kubesy; Faisal Abdelsamad Torad; Ibrahim Abdelsattar Saleh (Cairo : Mohamed Elsaid Abdelrahman Ali, 2019)
Cardiorespiratory diseases represent a large proportion of the internal medicine cases in small animal practice. About one tenth of small animal patient in daily practice suffer from cardiac disease. Electrocardiogram serves as an indispensable tool in evaluating cardiac patients. In this study we formulate three research experiments, First, we used 22 German shepherd puppies with Canine parvovirus type 2 . The purpose of this study was to evaluate the prognostic usefulness of epidemiological, hemato-biochemical and electrocardiogram (ECG) findings in German shepherd puppies with canine parvovirus (CPV). Mortality rate among these puppies was twenty-seven percent. This study suggested that age, platelet count, serum potassium, and T-wave length are useful for predicting the final outcome of hospitalized German shepherd puppies with CPV. Second experiment was done evaluate changes of electrocardiogram associate with degenerative mitral valve disease (DMVD). Sixteen dogs were enrolled in this study. 10 dogs suffered from DMVD and 6 dogs used as a control group. Forty percent of diseased dogs have left atrial enlargment (LAE) , on ECG, 6 dogs have abnormal P wave (increase in width or bifid or increase in both width and length). J wave didn't show up in any control dogs while appeared four times within DMVD dogs. Troponin-I was positive in 4 occasions all were diseased. J- wave didn't show any signficance with any disease parameter except age suggesting its age related appearance even without any disease
Thesis (Ph.D.) - Cairo University - Faculty of Veterinary Medicine - Department of Internal Medicine and Infectious Diseases
Issued also as CD
Keywords: Canine parvovirus; cTn-I; Prognosis